PENGARUH ZIKIR TAREKAT SYATTARIYYAH DALAM PEMBENTUKAN KEPRIBADIAN SANTRI DI PONDOK PESANTREN AR-RAMLY GIRILOYO WUKIRSARI IMOGIRI BANTUL - Siswoyo Aris Munandar; Nur Hoiriyah (UIN Sunan Kalijaga Yogyakarta, 2020)
ABSTRACTThis article is entitled: The Effect of the Tariqah Syattariyyah Remembrance in the Formation of Santri Personality in the Ar-Ramly Islamic Boarding School Giriloyo Wukirsari Imogiri Bantul. The background of this study departs from the assumption that personality formation is not only through formal education but through the management of the heart. Through remembrance specifically able to guide a dirty and sick heart clean and healthy again. Ar-Ramly Islamic Boarding School is one of the Islamic boarding schools in the archipelago that has educational programs to form students who have good personalities by Islamic teachings. This study aims to reveal the effect of Tariqah Syattariyyah Remembrance in the Formation of Santri Personality in the Ar-Ramly Islamic Boarding School Giriloyo Wukirsari Imogiri Bantul. This study uses a qualitative approach using the field as an object and library source as supporting data. Data can be used using interview methods for caretakers of the Ar-Ramly Islamic Boarding School, students and the community around the cottage. The results of this study, first, under the leadership of KH. Ahmad Zabidi until now, the Tariqa Syattariyyah experienced a development starting with the bookkeeping of the practice book, the more widespread place of the daily practice of the Syattariyyah Congregation and the convening of the alumni observers of the Tariqa Syattariyyah in the Ar-Ramly Islamic Boarding School. Secondly, the implementation of the Tariqa Syattariyyah practice activities by the students of the Ar-Ramly Islamic Boarding School in forming good behavior results in a good relationship between fellow students and the surrounding community because of the realization of morals to God. The religious activities program will help the students in forming good personalities to establish harmony in mingling with the boarding school environment, family, and in the community. Keywords: Remembrance/ Zikir, Tariqa Syattariyyah, Personality ABSTRAKArtikel ini berjudul: Pengaruh Zikir Tarekat Syattariyyah dalam Pembentukan Kepribadian Santri di Pondok Pesantren Ar-Ramly Giriloyo Wukirsari Imogiri Bantul. Latar belakang penelitian ini berangkat dari asumsi bahwa pembentukan kepribadian tidak hanya melalui pendidikan formal saja, melainkan melalui pengelolaan hati. Melalui zikir secara khusus mampu membimbing hati yang kotor dan sakit kembali bersih dan sehat. Pondok Pesantren Ar-Ramly merupakan salah satu pondok pesantren di Nusantara yang mempunyai program-program pendidikan sehingga dapat membentuk para santri memiliki kepribadian baik yang sesuai dengan ajaran-ajaran Islam. Kajian ini bertujuan untuk mengungkap Pengaruh Zikir Tarekat Syattariyyah dalam Pembentukan Kepribadian Santri di Pondok Pesantren Ar-Ramly Giriloyo Wukirsari Imogiri Bantul. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan lapangan sebagai objek dan sumber pustaka sebagai pendukung data. Data di dapat menggunakan metode wawancara kepada pengasuh Pondok Pesantren Ar-Ramly, santri dan masyarakat sekitar pondok. Adapun hasil penelitian ini, pertama, di bawah kepemimpinan KH. Ahmad Zabidi sampai sekarang, Tarekat Syattariyyah mengalami perkembangan dimulai dengan adanya pembukuan kitab amalan, semakin luasnya tempat pelaksanaan amalan harian Tarekat Syattariyyah dan terselenggaranya pertemuan alumni pengamal Tarekat Syattariyyah di Pondok Pesantren Ar-Ramly. Kedua, Terlaksananya kegiatan amalan Tarekat Syattariyyah oleh para santri Pondok Pesantren Ar-Ramly dalam membentuk perilaku yang baik menghasilkan hubungan yang baik antara sesama santri dan masyarakat sekitar di karenakan terwujudnya akhlak kepada Allah. Program kegiatan keagamaan nantinya akan membantu santri dalam membentuk kepribadian baik sehingga menjalin keharmonisan dalam berbaur dengan lingkungan pondok pesantren, keluarga, maupun dalam masyarakat. Kata Kunci: Zikir, Tarekat Syattariyyah, Kepribadian